Corporate Governance, Growth Opportunities dan Konservatisme Akuntansi: Bukti Empirik pada Perusahaan Manufaktur di Bursa Efek Indonesia - Jacobus Widiatmoko; Maria Goreti Kentris Indarti; Chika Adelia Agustin (Universitas Katolik Soegijapranata Semarang, 2020)
The purpose of this study was to examine the effect of institutional ownership, managerial ownership, and growth opportunities on accounting conservatism. This study uses two control variables, namely profitability and leverage. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample selection using the purposive sampling technique resulted in 246 data. The test results with ordinary least square regression indicate that institutional ownership has a positive effect on accounting conservatism. Institutional shareholders become an effective supervisory mechanism so that management will act conservatively. On the other hand, managerial ownership shows the opposite result of the hypothesis, and growth opportunities have no effect on accounting conservatism. As predicted, profitability as a control variable has a positive effect on accounting conservatism, but leverage has no effect on accounting conservatism.